EXPOSURE OF OPERATORS TO CHAINSAW VIBRATION IN FOREST HARVESTING - Jesus, André Tavares; Fiedler, Nilton César; Carmo, Flávio Cipriano de Assis do; Juvanhol, Ronie Silva (Floresta, 2020)
The implementation process of mechanized systems which occurred in the last decades in Brazil has brought numerous benefits of profitability, quality and safety for forestry activities. However, mechanization can cause harmful effects to the health of operators, among which include the excess of vibration that is responsible for numerous disorders such as Raynaud’s syndrome. The objective of this study was to evaluate the degree of exposure to vibration of chainsaw operators in cutting eucalyptus trees on farms. Thus, a portable accelerometer with a triaxial attachment positioned at the fingers of the operators was used to measure the data. The methodology proposed by NHO-10 was used to classify the degree of exposure. According to the results, 55% of the operators presented above the acceptable levels of exposure, requiring interventions which enable reduced hand-arm vibration. The vibration effects were observed to be more severe in the left hand socket of the operators. Based on the obtained results, it is concluded that there is a need for preventive and corrective measures which reduce the exposure of the operators as an intervention in the design of the machines, more rotation between operations, and greater care with the maintenance of the machines, training and reduced exposure time.